Modeling Work-Family Conflict Among Workforces Engaged in Long Distance Relationship: Moderated By Emotional Quotient - Abd Halim, Siti Noorhaslina; Mohamad Razali, Nur Hanisah; Kamaruddin, Faten Elina; Rahmat, Ainol Mardhiyah; Muda, Muhammad Haris Naqiuddin; Zainodin, Amir Imran (Advances in Social Sciences Research Journal, 2025)
Around the globe, evidence shows the growing number of married couples are living separately from one another. They are married to each other but stay apart for work reasons and meet at least once a week. In Malaysia, there are over 500,000 spouses who live separately due to employment demands. At present the country’s evidence is staggering records of declines in marriages and rising divorce cases in 2022, triggering curiosity about whether being in a long-distance relationship leads to work-family conflict. Long-distance relationships come with their unique challenges, and loneliness is one of the triggering factors. Present theories relevant to work-family conflict are still insufficient to explain further long-distance relationships. To the fact that present studies have shown that some long-distance marriages are as not as successful as live-together marriages, a study of whether emotional quotient moderates the relationship between loneliness and work-family conflict using a quantitative approach is warranted for investigation. This research output will provide in-depth knowledge on how the ability to understand, use, and manage one’s emotions will moderate the relationship between loneliness and work-family conflict. The study is aligned with Malaysia MADANI core values of ‘Prosperity’ and Peace in Islam that encourage dual-earner families towards tranquility and peaceful living without work-family conflict.